Forage Nutritive Value and Preference of Cool‐Season Grasses under Horse Grazing. (1st May 2013) - Allen, Elizabeth; Sheaffer, Craig; Martinson, Krishona
Abstract : Cool‐season grasses are rarely evaluated under horse grazing. The objectives of this study were to evaluate preference and forage nutritive value of cool‐season grasses while grazed by horses ( Equus caballus L.). Research was conducted in 2010 and 2011 in Minnesota. Four horses rotationally grazed tall fescue [ Schedonorus phoenix (Scop.) Holub], meadow fescue [ Schedonorus pratensis (Huds.) P. Beauv.], quackgrass [ Elymus repens (L.) Gould], smooth bromegrass ( Bromus inermis Leyss.), meadow bromegrass ( Bromus biebersteinii Roem. & Schult.), reed canarygrass ( Phalaris arundinacea L.), perennial ryegrass ( Lolium perenne L.), timothy ( Phleum pratense L.), Kentucky bluegrass ( Poa pratensis L.), creeping foxtail ( Alopecurus arundinaceus Pior.), and orchardgrass ( Dactylis glomerata L.) monthly during the growing season. Kentucky bluegrass, timothy, and meadow fescue were the most preferred grasses, with most grazing events removing >60% of the available forage, while meadow bromegrass, creeping foxtail, reed canarygrass, and orchardgrass were less preferred, with grazing removing <50% of available forage ( P ≤ 0.0027). Perennial ryegrass, quackgrass, and smooth bromegrass had a higher concentration of crude protein than Kentucky bluegrass, orchardgrass, creeping foxtail, or timothy ( P ≤ 0.0027). Quackgrass had a lower neutral detergent fiber (NDF) concentration than creeping foxtail or smooth bromegrass ( P = 0.0001). Perennial ryegrass and meadow fescue were higher in NDF digestibility, while creeping foxtail and Kentucky bluegrass were lower ( P = 0.0001). Timothy, Kentucky bluegrass, meadow fescue, and perennial ryegrass had higher nonstructural carbohydrate (NSC) concentrations than meadow bromegrass, orchardgrass, or reed canarygrass ( P ≤ 0.0001). Horses showed distinct preferences among grasses; however, only NSC was positively correlated with horse preference.